Malva sylvestris L. Protects from Fluoride Nephrotoxicity in Rat - A Babai Zarch; H Fallah Huseini; S Kianbakht; P Changaei; A Mirjalili; J Salehi (Institue of Medicinal Plants, ACECR, 2017)
Background: Malva sylvestris L. (M. sylvestris) has antioxidant property and is widely used in the traditional medicine to treat gastrointestinal, respiratory, skin and urological disorders. Objective: In this study, the protective effect of M. sylvestris against sodium fluoride-induced nephrotoxicity in the rat was evaluated. Methods: The M. sylvestris flower extract was prepared and injected intraperitoneally at the doses of 100, 200, 400 mg/kg/day to rat groups (10 in each group) for 1 week and subsequently 600 ppm sodium fluoride was added  to the rats drinking water for 1 additional week. After these steps, the rat serum levels of urea, creatinine, reduced glutathione, catalase and malondialdehyde were determined. The histopathology of the rats' kidney was also studied. In this study, vitamin C (10 mg/kg/day) was used as positive control. Results: Sodium fluoride administration increased levels of BUN, creatinine, glutathione, catalase activity and decreased malondialdehyde levels indicating induction of nephrotoxicity in the rats. M. sylvestris extract pretreatment significantly decreased the BUN and creatinine levels (P<0.05). Catalase activity and glutathione levels were significantly increased by M. sylvestris (P<0.05). All three doses of the M. sylvestris decreased the malondialdehyde level, but it was significant only for the dose of 400 mg/kg/day (P<0.05). The Malva sylvestris effects were comparable with those of vitamin C. Histopathological findings also showed protective effects of M. sylvestris against the renal damage induced by sodium fluoride. Conclusion: The results suggest that M. sylvestris has protective effects against sodium fluoride-induced nephrotoxicity which maybe mediated by the antioxidant activity of the plant flavonoids.